Ecological considerations for gene drive systems - Lanzaro, Gregory C. (Henry Stewart Talks, 2018)
Gene drive technology used for the elimination of malaria in Africa, Evaluation and deployment of genetically engineered mosquitoes (GEM) with gene drive into natural malaria-transmitting mosquito populations, Fitness of GEM relative to their wild counterparts, Strategies for maintaining and evaluating overall fitness, Criteria for the establishment of field trial sites for the release and evaluation of GEM, Implementation of GEM for malaria elimination/eradication at the continental scale